Overview of Malaria Incidence Based on Secondary Data in Asmat Regency, South Papua: 2010-2022 - Ade Sri Wahyuni; Selfin Dwiyanti (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Malaria is an infectious disease caused by the Plasmodium parasite and transmitted through the bite of Anopheles mosquitoes. It remains a significant global health problem and continues to be a major public health concern in Indonesia. Although the national incidence rate has shown a declining trend, certain regions particularly in eastern Indonesia still report high case numbers. Asmat Regency in South Papua is one of the areas that is significantly affected. This study aims to provide an overview of malaria incidence trends in Asmat Regency based on available secondary data. Objective: To describe the trends and characteristics of malaria incidence in Asmat Regency based on secondary data from the Asmat Regency Health Office. Method: This study employed a quantitative descriptive design using secondary data obtained from the Asmat Regency Health Office. Data were analyzed descriptively and presented in tables and graphs. Results: The analysis revealed fluctuations in laboratory-confirmed malaria morbidity rates over the observed years. The graphical trends indicate periods of notable increases and decreases, although the incidence unit (case rate/CR) was not specified. Conclusion: The malaria morbidity rate in Asmat Regency demonstrates complex fluctuation patterns. Further research with more comprehensive datasets and in-depth analysis is required to identify the contributing factors and to assess the effectiveness of existing malaria control programs. Keywords: Malaria, Anopheles, Plasmodium, Asmat Regency, South Papua, Indonesia